Efficacy and safety of the "mother's kiss" technique: a systematic review of case reports and case series. - Cook, S; Burton, M; Glasziou, P (2012)
BACKGROUND: Foreign bodies lodged in the nasal cavity are a common problem in children, and their removal can be challenging. The published studies relating to the "mother's kiss" all take the form of case reports and case series. We sought to assess the efficacy and safety of this technique. METHODS: We performed a comprehensive search of the Cochrane library, MEDLINE, CINAHL, Embase, AMED Complementary and Allied Medicine and the British Nursing Index for relevant articles. We restricted the results to only those studies involving humans. In addition, we checked the references of relevant studies to identify further possibly relevant studies. We also checked current controlled trials registers and the World Health Organization search portal. Our primary outcome measures were the successful extraction of the foreign object from the nasal cavity and any reported adverse effects. We assessed the included studies for factors that might predict the chance of success of the technique. We assessed the validity of each study using the Newcastle-Ottawa scale. RESULTS: Eight relevant published articles met our inclusion criteria. The overall success rate for all of the case series was 59.9% (91/152). No adverse effects were reported. INTERPRETATION: Evidence from case reports and case series suggests that the mother's kiss technique is a useful and safe first-line option for the removal of foreign bodies from the nasal cavities of children.